2020
DOI: 10.1007/s00148-020-00791-5
|View full text |Cite
|
Sign up to set email alerts
|

Safety at work and immigration

Abstract: This paper examines the effect of immigration on workplace safety, an understudied outcome in the literature. We use a novel administrative dataset of the universe of workplace accidents reported in Spain from 2003 to 2015 and follow an instrumental variables (IV) strategy based on the distribution of early migrants across provinces. Our results show that the massive inflow of immigrants between 2003 and 2009 reduced the number of workplace accidents by 10,980 for native workers (7% of the overall reduction du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
0
6
0
2
Order By: Relevance
“…Taking into consideration this potential endogeneity problem, we also estimate the relationship between immigration and the shadow economy by adopting a two‐stage least square (2SLS) approach, which requires an instrument for the immigration variable. The choice of this instrument is based on a specific strategy that has been widely used in the literature (see Basso et al., 2019; Bellés‐Obrero et al., 2021; Bianchi et al., 2012; Card, 2001, 2005; D'Amuri & Peri, 2014; Edo et al., 2019; Lonsky, 2021; Rozo & Sviatschi, 2021). We use an instrument à la Bartik (1991) to control for the “assortative matching” of immigrants into localities with larger availability of irregular jobs.…”
Section: Empirical Analysismentioning
confidence: 99%
“…Taking into consideration this potential endogeneity problem, we also estimate the relationship between immigration and the shadow economy by adopting a two‐stage least square (2SLS) approach, which requires an instrument for the immigration variable. The choice of this instrument is based on a specific strategy that has been widely used in the literature (see Basso et al., 2019; Bellés‐Obrero et al., 2021; Bianchi et al., 2012; Card, 2001, 2005; D'Amuri & Peri, 2014; Edo et al., 2019; Lonsky, 2021; Rozo & Sviatschi, 2021). We use an instrument à la Bartik (1991) to control for the “assortative matching” of immigrants into localities with larger availability of irregular jobs.…”
Section: Empirical Analysismentioning
confidence: 99%
“…Almost 40 percent of recent immigrants are from Asia (especially Southeast Asia), and a roughly equal number originate in Mexico, the Caribbean and Latin America. 1 Most immigrants, therefore, come from countries that are poorer and less educated than the United States. Table 2 also shows the share of 1980s immigrants from each region who have less than a high school education.…”
Section: Immigration Factsmentioning
confidence: 99%
“…Alacevich and Nicodemo (2019) find that immigration led to reductions in natives' injury rates in Italy and report suggestive, although not statistically significant, evidence that changes in the physical intensity of natives' occupations underlies the observed effect. Bellés-Obrero, Bassols, and Castello (2020) find that increased immigration caused the number of workplace accidents among natives to fall in Spain as natives shifted to communications-intensive occupations from manual occupations. Giuntella and Mazzonna (2015) find that immigration improved natives' health outcomes in Germany as a result of improvements in natives' working conditions.…”
mentioning
confidence: 89%
“… 2 Several studies examine questions related to whether immigration affected European natives’ exposure to occupational risks. Alacevich and Nicodemo (2019) examined Italy; Bellés-Obrero, Bassols, and Castello (2021) examined Spain; Giuntella and Mazzonna (2015) examined Germany; and Giuntella, Mazzonna, Nicodemo, and Vargas-Silva (2019) examined the United Kingdom. All of these studies found results consistent with natives moving into safer jobs. …”
mentioning
confidence: 99%